PENGARUH PENGETAHUAN PERPAJAKAN, KETEGASAN SANKSI, KUALITAS PELAYANAN PETUGAS PAJAK DAN PENERAPAN E – FILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Achmad Basuki; Jaeni (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this study was to determine whether knowledge of taxation, firmness of sanctions, service quality of tax officers and the application of E-filling had a significant effect on individual taxpayer compliance at MSME Pratama South Semarang. The sample in this study were 100 respondents at KPP Pratama South Semarang. Methods of data collection using a questionnaire. Sampling method used is simple random sampling and the data analysis model used is multiple linear regression analysis. The results showed that knowledge of taxation, firmness of sanctions, service quality of tax officers, and the application of e-filling had an effect on MSME taxpayer compliance. Simultaneously, the variable knowledge of taxation, firmness of sanctions, service quality of tax officers and the application of e-filling affect the compliance of MSME taxpayers.